Dj1 deficiency protects against atherosclerosis with anti-inflammatory response in macrophages - Tharini Sivasubramaniyam; Jiaqi Yang; Henry S. Cheng; Alexandra Zyla; Angela Li; Rickvinder Besla; Idit Dotan; Xavier S. Revelo; Sally Yu Shi; Helen Le; Stephanie A. Schroer; David W. Dodington; et al. (Scientific Reports, 2021)
Abstract Inflammation is a key contributor to atherosclerosis with macrophages playing a pivotal role through the induction of oxidative stress and cytokine/chemokine secretion. DJ1, an anti-oxidant protein, has shown to paradoxically protect against chronic and acute inflammation. However, the role of DJ1 in atherosclerosis remains elusive. To assess the role of Dj1 in atherogenesis, we generated whole-body Dj1-deficient atherosclerosis-prone Apoe null mice (Dj1 −/− Apoe −/− ). After 21 weeks of atherogenic diet, Dj1 −/− Apoe −/− mice were protected against atherosclerosis with significantly reduced plaque macrophage content. To assess whether haematopoietic or parenchymal Dj1 contributed to atheroprotection in Dj1-deficient mice, we performed bone-marrow (BM) transplantation and show that Dj1-deficient BM contributed to their attenuation in atherosclerosis. To assess cell-autonomous role of macrophage Dj1 in atheroprotection, BM-derived macrophages from Dj1-deficient mice and Dj1-silenced macrophages were assessed in response to oxidized low-density lipoprotein (oxLDL). In both cases, there was an enhanced anti-inflammatory response which may have contributed to atheroprotection in Dj1-deficient mice. There was also an increased trend of plasma DJ-1 levels from individuals with ischemic heart disease compared to those without. Our findings indicate an atheropromoting role of Dj1 and suggests that targeting Dj1 may provide a novel therapeutic avenue for atherosclerosis treatment or prevention.